Waste Management of Silk Cocoons Residue by Using Innovation to Develop Lifestyle Fashion Products with a Sustainability Concept - Raksuan, Kamonbhat; Urusetthanon, Somkiet; Kampeerapappun, Piyaporn (RMUTK Journal of Liberal Arts, 2025)
The objectives of the research were 1) to solve the problems of cocoon residue waste generated by the textile, fashion, and garment industry. 2) to use creative innovation upcycling and add value from silk cocoon scraps. 3) to develop lifestyle fashion product design from a sustainable concept. This research was an experimental and qualitative study. The sample group was consisted of 3 experts selected by purposive sampling. The research instruments included in-depth interviews, analysis of experimental data in tabular form, and qualitative data analysis through content analysis. The results found that 1) waste silk thread from the fashion and textile industry was successfully transformed into filaments and threads through a recycling process. The tensile strength and elongation at break of the yarns were tested according to ASTM D2256-97 standards. The breaking strength of the fabric was tested according to ASTM 5035-90 standards, and its tear resistance was tested according to ASTM 1424-83 standards. Subsequently, the 5 Ne yarn was woven into 3/1 twill fabric, exhibiting a canvas-like texture or calico fabric. 2) the results of using innovative methods to enhance the value of waste silk, through testing the fabric’s strength according to ASTM D-1388-08 standards, revealed that the treated fabric with different concentrations of antibacterial agents did not affect the strength and color of the fabric. Additionally, the treated fabric showed slightly stiffer than that of untreated fabric. The antibacterial properties against two types of bacteria, E. coli and S. aureus, were tested and displayed that they effectively inhibited the growth of S. aureus at a concentration of 20 g/L. The water absorption according to AATCC-792018 standards demonstrated good absorbency. Moreover, after undergoing 20 cycles of washing, the treated fabric retained the effectiveness. It also indicated good performance even after laundry. 3) The results of developing sustainable fashion products, based on interviews and analysis, revealed that clothing should be meet the needs of Generation Z consumers. The clothing should be able to transform (Transformation clothing) and be easy to care. The design should be fashionable and distinctive and enable the wearer to feel confident in expressing their identity on social media. Consequently, 10 clothing designs were created under the theme of ‘Blending the Nature for Sustainability’. The fabric derived from this research was used to make blue jeans denim which is popular in fashion and textile industry.